Faktor-Faktor yang Mempengaruhi Peyakit Diabetes Melitus di Kota Palu - Musjaya M.; Ayu Dia Agustina; Nur Annisa Safirah; Ardiputra, Muh. Akbar; Sardi, Bambang; Saifah, Andi; Putra, Suwarty Nursahara Usman (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Diabetes mellitus is a metabolic disorder caused by insufficient production of the hormone insulin by the pancreas. This disease can be said to be a chronic disease because it can occur over a long period . This research is about the factors that influence Diabetes Melitus disease in Palu City. This study aims to determine the description of patient visits suffering from Diabetes Melitus at the Central Sulawesi Provincial Laboratory. The sampling technique uses the purpose sampling method, namely purposeful sampling or sampling carried out with subjects based on criteria set by the researcher. The results of this study analyze the factors that influence Diabetes Melitus disease in Palu City. The research result obtained were that there were more women with 288 people and 132 men. Meanwhile, in 2024 from January to march, there will be 90 women and 44 men, the number of patients suffering from diabetes melitus. Namely those aged 46-55 ini 2023 there will be 240 people and ini 2024 there will be 143 people with diabetes melitus agen 40-59 person. The gender factor is that there are more female sufferers of diabetes mellitus compared to male sufferers